Experimental Study on Capillary Floor Radiation Heating System with Air Source Heat Pump - 牛建会; 王海超; 吕天舒; 李永亮 (Zhileng xuebao, 2025)
The air source heat pump capillary radiant floor heating system directly heats the floor with refrigerant as the heat medium, which has the advantages of simple system and good heat transfer effect. In this paper, an experimental device of capillary floor radiant heating with air source heat pump is built, and the heating experiment of parallel capillary floor radiant ends is carried out at different outdoor ambient temperatures. The experimental results show that the lower the outdoor temperature, the longer the time required for the temperature stability of the capillary floor radiation end. When the outdoor temperature is -5 °C, the stability time is 120 min; the temperature difference between the exhaust inlet end and the condensate outlet end on the same capillary wall is large. The temperature difference on the capillary wall can reach 6.40 °C, and the temperature difference on the surface of the 20 mm thick cement floor can reach 4.20 °C. The vertical temperature difference from the capillary wall to the cement floor surface is small, not exceeding 0.40 °C, and the vertical heat transfer effect of the floor is good. The temperature difference at the same position of different capillaries is within 0.80 °C, and the temperature uniformity is good. When the outdoor temperature is-5 °C, the heating COP of the unit can reach 4.6 with a good heating performance.